Ent-Peniciherqueinone Suppresses Acetaldehyde-Induced Cytotoxicity and Oxidative Stress by Inducing ALDH and Suppressing MAPK Signaling - Taehoon Oh; Mincheol Kwon; Jae Sik Yu; Mina Jang; Gun-Hee Kim; Ki Hyun Kim; Sung-Kyun Ko; Jong Seog Ahn (MDPI AG, 2020)
Studies on ethanol-induced stress and acetaldehyde toxicity are actively being conducted, owing to an increase in alcohol consumption in modern society. In this study, ent-peniciherqueinone (EPQ) isolated from a Hawaiian volcanic soil-associated fungus Penicillium herquei FT729 was found to reduce the acetaldehyde-induced cytotoxicity and oxidative stress in PC12 cells. EPQ increased cell viability in the presence of acetaldehyde-induced cytotoxicity in PC12 cells. In addition, EPQ reduced cellular reactive oxygen species (ROS) levels and restored acetaldehyde-mediated disruption of mitochondrial membrane potential. Western blot analyses revealed that EPQ treatment increased protein levels of ROS-scavenging heme oxygenase-1 and superoxide dismutase, as well as the levels of aldehyde dehydrogenase (ALDH) 1, ALDH2, and ALDH3, under acetaldehyde-induced cellular stress. Finally, EPQ reduced acetaldehyde-induced phosphorylation of p38 and c-Jun N-terminal kinase, which are associated with ROS-induced oxidative stress. Therefore, our results demonstrated that EPQ prevents cellular oxidative stress caused by acetaldehyde and functions as a potent agent to suppress hangover symptoms and alcohol-related stress.